A Transitivity Study of Gilbert Blythe’s Characters in Anne with an E Series - Salma Andini, Anggi Nazliza; Candria, Mytha (Politeknik Negeri Sriwijaya, 2024)
This research investigates the characterization of Gilbert Blythe, the main male character of Anne with an E series, produced by Moira Walley-Beckett and aired by Netflix in 2017, 2018, and 2019. The primary purpose of this qualitative study is to examine the transitivity processes used to portray Gilbert Blythe’s personality traits in three seasons of the series. By utilizing Halliday’s transitivity theory (2014), this study focuses on clauses where Blythe appears as participants or circumstantial elements. Data were collected through document-analysis method and note-taking technique. The results indicate that Blythe is adventurous, determined, confident, and considerate. The traits are communicated through material, mental, relational, verbal, and behavioural processes, with material process the most prominent. The predominance of the material process suggests that Blythe is an active character who takes action to pursue new experiences and work toward his chosen vocation. It also reflects the emphasis on physical actions, particularly in how Blythe interacts with and assists other characters in disadvantaged situations